Community college students' experiences of mental-health stigma: a phenomenological study - Andrade, Angela, author; Anderson, Sharon K., advisor; Kuk, Linda, committee member; Miller, Lisa, committee member; MacQuiddy, Susan, committee member (Colorado State University. Libraries, 2015)
Campus acts of violence, student suicide, and the relative increase in mental-health incidents among college students are several reasons that mental health is a pressing issue for higher education. Unfortunately, negative stigma surrounding mental-health issues impacts college students and their choices about seeking help. The purpose of this study was to explore the lived experiences of stigma for college students enrolled at a medium-sized public community college who self-identified with a mental-health issue. Research questions included the following: * How do students who self-identify with some mental-health issue experience stigma? * What kind of influence does stigma have on these students' willingness to seek help? * How do these students view others who a have mental-health problem in relation to stigma? * How do these students view themselves in relation to stigma? Results from two interviews with and responses to online prompts of six students indicated that they experienced social distance through being seen as outside of the social norm, hearing negative talk about mental health, being treated as fragile, and experiencing frequent bullying in high school. For these students, making the decision to seek help entailed navigating external pressure and internal denial. Students found support through connecting with others with mental-health struggles. Despite being seen as dangerous and facing stereotypes based on gender and diagnosis, all students in the study held a positive view of themselves and expressed compassion for others with mental-health problems. Results from the study confirm previous research and reveal emergent findings related to students' changes in beliefs in self-stigma and a hierarchy of stigma based on diagnosis. The study concludes with a discussion of implications for practice and future research.
Keywords: help-seeking behavior; stigma; mental health; college students